Rural Tourism Development in Jembayan Tengah Village East Kalimantan-Indonesia - Keliwar, Said; Musdalifah, Musdalifah; Dwiatmojo, A. Rinto (Technium Social Sciences Journal, 2022)
Rural areas have actually extremely varied perspectives, each the prospective of natural deposits, social sources of the neighborhood, in addition to innovative sources of the regional neighborhood. The variety of these sources could be industrialized as a country community-based tourist item to enhance the well-being of the community. For this reason, this research was actually carried out towards identity as well as evaluate the current prospective to become utilized as a community-based tourist town item in Jembayan Tengah East Kalimantan Indonesia. The method technique utilized within this particular research study is actually the Analytical Hierarchy Process (AHP) technique. This technique is actually utilized to analyze the concern range associated with elements of establishing traveler town beauty, community centers as well as tourist centers, tourist ease of access, as well as promo, in Jembayan Tengah East Kalimantan Indonesia. The outcomes revealed that the beauty element was actually one of the absolute most focused on elements along with the greatest rack up of 0.564 when compared with various other elements, specifically centers, promo elements, and ease of access. While the requirements that end up being the concern of advancement are actually the requirements for all-organic tourist destinations along with the greatest 0.495 when compared with various other requirements, specifically the requirements for transport centers, tourist centers, as well as promo utilizing digital media.